2013
DOI: 10.6106/jcepm.2013.3.4.020
|View full text |Cite
|
Sign up to set email alerts
|

Variation Determinants in Building Construction: Ghanaian Professionals Perspective

Abstract: Variation in construction means modification of design, changes in quality, quantity of work including the alteration of standard of materials or goods to be used in the work and the removal from site any kind of material not in accordance in the contract. In Ghana, Variation order has become major issue in the construction industry. This had resulted in cost overruns, delay and in some contracts dispute, between parties. The aim of this paper was to identify the root causes of variation; effects of variations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 9 publications
1
11
0
Order By: Relevance
“…The learning corresponds with knowledge sharing among designers and CAD/BIM corresponds with the use of computer programs. The result also agrees with Asamaoh & Offei-Nyako (2013) in respect of reports among consultants and use of oversight committee for designs. Reports among designers goes with knowledge sharing among designers and use of oversight committees goes with rechecking design documents by the committees before presenting them for use.…”
Section: Solutions To Design-error-induced Variation In Building Projsupporting
confidence: 79%
See 1 more Smart Citation
“…The learning corresponds with knowledge sharing among designers and CAD/BIM corresponds with the use of computer programs. The result also agrees with Asamaoh & Offei-Nyako (2013) in respect of reports among consultants and use of oversight committee for designs. Reports among designers goes with knowledge sharing among designers and use of oversight committees goes with rechecking design documents by the committees before presenting them for use.…”
Section: Solutions To Design-error-induced Variation In Building Projsupporting
confidence: 79%
“…For instance, while the client wants value for money, the contractor wants to maximize profit. These interests normally lead to design error as a major source of variation, as claimed by Asamaoh & Offei-Nyako (2013).…”
Section: Introductionmentioning
confidence: 99%
“…From the literature review, it is found that there are 18 main causes of the variation works identified by most researches ( [5], [6], [2], [7], [3], [8], [9], [10], [11], [12], [13], [14], [15], [16] and [17]). The causes of variation order are described as follows:…”
Section: The Causes Of Variation Workmentioning
confidence: 99%
“…Errors and omissions in design: Errors and omissions in design are a significant cause of project delays [9]. Dependent upon the timing of the errors in the project, delays and variations may occur [13], work changes are a key issue in the construction industry in Ghana and are largely due to client design changes.…”
Section: The Causes Of Variation Workmentioning
confidence: 99%
See 1 more Smart Citation